Sepsis beyond bundles: contextualising paediatric care in resource-limited settings through situational analysis - John Adabie Appiah; Leah Ratner; Sheila Agyeiwaa Owusu; Ahmet Uluer; Gustav Nettey; Allysa Warling; Charles Martyn-Dickens; Emma Otchere; R. Elaine Cagnina; Maame Fremah Kotoh- Mortty; Eugene Martey (BMJ Paediatrics Open)
Background Paediatric sepsis remains a significant contributor to morbidity and mortality, particularly in low- and middle-income countries (LMICs), where healthcare resources are often limited. Paediatric sepsis bundles, which include prompt administration of antibiotics, fluid resuscitation and continuous organ function monitoring, are crucial for improving outcomes, especially when initiated within the first ‘golden hour’ of sepsis recognition. These bundles, adapted from adult sepsis care protocols through the Surviving Sepsis Campaign, are increasingly emphasised in global sepsis management guidelines. However, the implementation of these protocols in LMICs is challenged by resource limitations and systemic barriers.Methods This situational analysis, conducted at two hospitals in Ghana—a tertiary facility and a district (secondary) facility—maps the availability of critical resources for paediatric sepsis care through a structured environmental scan using survey methodology. We assess staffing levels, access to medications, airway support and diagnostic capabilities. Methods were conceptualised through inner and outer settings of the Consolidated Framework for Implementation Research (CFIR) and reported through the Donabedian model for healthcare quality.Results This study compared paediatric care at a tertiary hospital (Komfo Anokye Teaching Hosptial (KATH)) and a district hospital (Presbyterian Hospital, Agogo (PreHA)) in Ghana, highlighting KATH’s emergency and intensive care unit (ICU) services, specialised staff and broader respiratory support. PreHA, although without a paediatric-specific ICU, leveraged research funding to enhance clinical care capacity. Both hospitals experienced regular power outages but had reliable generators, and while they offered basic medications and treatments, resource limitations, including out-of-pocket costs for families, impacted access to essential medications and laboratory tests.Conclusion Concerns around resource availability, compounded by structural determinants such as financial barriers and historical underfunding hypothesised to be rooted in colonialism, highlight the need for context-sensitive adaptations of paediatric sepsis bundles. Our findings underscore the importance of a participatory approach to guideline adaptation and resource distribution, incorporating local expertise and addressing structural inequities to improve paediatric sepsis outcomes in Ghana. Future qualitative research will explore pre- and peri-hospital barriers to care and inform more effective, contextually appropriate interventions.